Dinamika Relasi Negara dan Civil Society dalam Pembangunan Perdamaian di Ambon 2002-2022 - Wally, Fadly Fahry S.; Kosandi, Meidi (JPP (Jurnal Politik Profetik), 2025)
This article analyzes the dynamics of the relationship between the state and civil society in the peacebuilding process in post-conflict Ambon from 1999 to 2002. Using J.P. Lederach's conflict transformation theory framework and Pierre Bourdieu's social capital concept, this study explores the evolution of the relationship between the two actors during the period from 2002 to 2022. A qualitative research method with a case study approach is used to analyze the processes of reconciliation, rehabilitation, and social reconstruction. The findings show that the state-civil society relations have transformed from a hierarchical-centralist pattern to a collaborative-participative one. Civil society acts as a bridge in building trust among groups, while the state provides legal frameworks and structural support. The social capital accumulated through interfaith dialogues, joint economic programs, and cultural initiatives has proven effective in strengthening social cohesion and preventing escalation of horizontal conflicts in Ambon.